PHYTOCHEMICAL ANALYSIS, ANTIOXIDANT PROPERTIES AND PHENOLIC ACIDS DETERMINATION OF DATE PALM (Phoenix dactylifera L.) LEAVES AND ROOTS EXTRACTS - Hamini, Faiza; Yousfi, Mohamed; Soumaya, Hachani (Journal of the Chilean Chemical Society, 2025)
The date palm (Phoenix dactylifera L.) is a vital phytogenetic resource in arid regions. The roots and leaves are traditionally used for various purposes, including medicine. Despite extensive research on date palm fruits, the biochemical properties of its by-products remain underexplored. This study investigates the bioactive compounds in the leaves and roots of date palm cultivars. A reflux apparatus was used to extract total phenolic content (TPC), measured using the Singleton and Rossi method, while total flavonoid content (TFC) was determined using aluminum trichloride. Antioxidant activity was assessed using the DPPH assay, and HPLC-DAD analysis identified and characterized phenolic acids. The results revealed very high TPC levels in both leaves and roots supporting their traditional uses, reaching up to 825.63 ± 0,1 mg GAE/100 g dry weight in TAD leaves. TFC ranged from 18.81±0,15 to 117.85±0,2 mg EQ/100 g dry weight and correlated significantly with TPC. The extracts demonstrated significant antiradical efficacy compared to vitamin C, suggesting that all parts of the date palm are excellent sources of natural antioxidants. Twelve cell wall-bound and soluble phenolic acids were identified, several of which were previously unreported in this plant. Leaves predominantly contained ferulic acid, p-coumaric acid, and sinapic acid, while roots were rich in p-hydroxybenzoic acid. Additionally, several hydroxybenzoic and hydroxycinnamic acids implicated in plant defense mechanisms were identified. These findings highlight the dual importance of conserving local plant biodiversity and exploring date palm phenolics for applications in food, pharmaceuticals, and organic agriculture.Haut du formulaireBas du formulaire